Migrasi Pekerja 'Metu' di Desa Patokpicis Kecamatan Wajak Kabupaten Malang: Migration of 'Metu' Workers in Patokpicis Village, Wajak District, Malang Regency - Ahmad Junaidi (Fenomena, 2011)
-Upon closer observation, the rapid population growth in the Malang region is not solely due to birth rates but also urbanization factors. Urbanization, as agreed upon by experts, is one way to alter one's status. This is because the trade exchange value of the rural agricultural sector, including wage levels for minimally land-owning farm laborers, is far lower than in urban areas. The density of urban populations is further evident due to the influx of migrant workers employed across various sectors. These migrant workers typically originate from villages surrounding the city. Migrant workers or "metu" workers (a term for migrant workers in Patokpicis Village, Wajak, Malang) will be examined in this research, particularly concerning social changes in Patokpicis. Jika diamati lebih jauh, pertumbuhan penduduk di wilayah Malang tidak hanya disebabkan oleh kelahiran, tetapi juga oleh faktor urbanisasi. Urbanisasi, sebagaimana disepakati oleh para ahli, merupakan salah satu cara untuk mengubah status. Hal ini terjadi karena nilai tukar dagang di sektor pertanian pedesaan, termasuk tingkat upah bagi buruh tani yang memiliki lahan minimal, jauh lebih rendah dibandingkan di kota. Kepadatan penduduk di kota semakin terlihat karena banyaknya pekerja migran yang bekerja di berbagai sektor pekerjaan. Pekerja migran ini umumnya berasal dari desa-desa sekitar kota. Pekerja migran atau pekerja metu (sebutan untuk pekerja migran di Desa Patokpicis, Wajak, Malang) akan dikaji dalam penelitian ini, khususnya yang berkaitan dengan perubahan sosial di Patokpicis.